Development of a Local Area Network with Netsupport in Learning in a Computer Laboratory - Putra, La Ode Alwin Syahputra; Effendi, Hansi; Hendriyani, Yeka; Ambiyar (AI Society & STMIK Indonesia, 2023)
Technological developments are increasingly advanced so as to increase the use of computer laboratories in higher education, especially in the learning process. However, this is not matched by the completeness of adequate infrastructure, which causes problems when using the laboratory. This study aims to develop and update a local area network with net support for learning in computer labs 5 and 6. This research uses the network development life cycle (NDLC) method. Data collected by questionnaire technique. The results of this study indicate that the validator test assessment from the innovation aspect of the IT infrastructure component is 89.17% so that the level of validity can be interpreted as valid in use, from the information system aspect it is 93.55%, so it can be interpreted as valid in use, practicality (group A) practicality test of 92.60%, so that it can be interpreted as practical to use, practicality (group B) practicality test is 94%, so the level of practicality can be interpreted as practical to use, practicality (Lecturer) practicality test is 95.23%, so that the practicality level can be interpreted as practical used, the effectiveness (group A) of the effectiveness test was 94.55%, so that the level of effectiveness could be interpreted as effectively used, the effectiveness (group B) of the effectiveness test was 93.70%, so the level of effectiveness could be interpreted as effectively used, effectiveness (labor assistant ) effectiveness test of 93.58%, so that the level of effectiveness can be interpreted as effectively used. So that it can be concluded that the development of a local area network network with netsupport in computer laboratory learning is feasible to use.